Politeness Strategies in Sasak Language: Avoiding Rudeness in Conversations with Elders - Sugianto, Sugianto; Tawali, Tawali (Journal of Language and Literature Studies, 2024)
This study explores the politeness strategies embedded in the Sasak language, spoken by the Sasak people of Lombok, Indonesia. These strategies reflect deeply rooted cultural norms emphasizing respect and harmony, particularly in interactions with elders. The Sasak people use a linguistic system known as undag bangse/bahase, or “language levels,” allowing speakers to adjust their language based on age, social relationship, and status. Through this system, communication aligns with Sasak cultural priorities, especially the value placed on avoiding conflict and maintaining social cohesion. A central feature of Sasak politeness is the use of indirect and deferential speech, enabling speakers to convey disagreement or decline requests subtly, minimizing confrontation and preserving harmony. This qualitative study, based on interviews with native speakers, reveals how these strategies not only support the diversity of Sasak dialects but also reinforce the community’s core cultural values. The Sasaknese language, influenced by historical and regional factors, remains distinct and resilient, reflecting the cultural heritage of Lombok in a rapidly modernizing world. Sasaknese language practices, marked by respect and indirectness, play a key role in expressing social identity and cultural wisdom, positioning the language as both a means of connection and a symbol of identity. This research highlights the Sasak people’s dedication to preserving cultural values through language, demonstrating how linguistic practices help sustain social harmony and cultural continuity.